2011
DOI: 10.1016/j.biombioe.2011.05.028
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the life cycle cost of rapeseed oil as a straight vegetable oil fuel to replace petroleum diesel in agriculture

Abstract: The use of straight vegetable oil (SVO) as biofuel has been recognized as a valid substitute of diesel fuel in the agricultural sector under specific circumstances. Its direct use reduces most of the chemical processes involved when converting it into biodiesel, thus lowering harmful emissions. This study presents the economic analysis of a selfsupply farming model that uses rapeseed as its fuel base. This model addresses agricultural environmental concerns and can even minimize dependence on the fluctuating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…These sectors are major consumers of fuel oils, either high distillates (diesel), medium distillates (DDO Distillate Diesel Oil) or heavy Fuel Oil 180 (FO180), which might be wholly or partially replaced with SVO [10,12,13]. This solution may contribute to reducing the cost of fossil fuel imports incurred by most developing countries, curb dependence on fossil fuels and limit greenhouse gas (GHG) emissions [14,[16][17][18]. This is particularly true for African countries such as Burkina Faso, Mali, Niger, Botswana, Madagascar, Malawi, Tanzania or Uganda, which import 100% of the fossil fuels they need [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sectors are major consumers of fuel oils, either high distillates (diesel), medium distillates (DDO Distillate Diesel Oil) or heavy Fuel Oil 180 (FO180), which might be wholly or partially replaced with SVO [10,12,13]. This solution may contribute to reducing the cost of fossil fuel imports incurred by most developing countries, curb dependence on fossil fuels and limit greenhouse gas (GHG) emissions [14,[16][17][18]. This is particularly true for African countries such as Burkina Faso, Mali, Niger, Botswana, Madagascar, Malawi, Tanzania or Uganda, which import 100% of the fossil fuels they need [19].…”
Section: Introductionmentioning
confidence: 99%
“…The most widespread scheme adopted by project promoters is the local production of oilseeds and their conversion into SVO by village-scale extraction units or decentralized cooperative mills, to fuel local stationary diesel engines [10,11,27]. This scheme has the advantage over biodiesel production of only requiring reasonable investments and offering much more flexibility in terms of production capacity, compared with large-scale centralized biodiesel production [17,20]. At the beginning of these biofuel promotion campaigns, the concerns mainly focused on the agricultural part of the sector.…”
Section: Introductionmentioning
confidence: 99%
“…SVO can be produced on-farm with minimal processing using a mechanical oilseed press and filter and used in a standard tractor with modifications to run on SVO (Baquero et al, 2011). The oilseed crop used to produce SVO fuel on an integrated crop-livestock farm can utilize manure nutrients to partly offset mineral fertilizers, while the oilseed meal can be used in livestock rations as an alternative to an imported protein source (Newkirk, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The oilseed crop used to produce SVO fuel on an integrated crop-livestock farm can utilize manure nutrients to partly offset mineral fertilizers, while the oilseed meal can be used in livestock rations as an alternative to an imported protein source (Newkirk, 2009). Considering both the tractor conversion and meal co-product value, SVO has been found to be more economically viable than biodiesel for small to mid-sized farms, but without subsidies was comparable or somewhat more expensive than petroleum diesel (Fore et al, 2011;Baquero et al, 2011). Previous studies have also shown that reducing pesticide use via best management practices can improve energy efficiency and reduce GHG emissions while remaining as or more productive than conventionally managed systems (Cruse et al, 2010;Alluvione et al, 2011;Crosson et al, 2011;Davis et al, 2012). In Iowa, using integrated pest management in low input, diverse farming systems resulted in significantly lower pesticide use and toxicity potential per system (Davis et al, 2012) and between 23% and 56% lower fossil energy input in those systems compared with a 2-year, conventionally managed, corn-soy rotation (Cruse et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such optimization is performed by means of a genetic algorithm-based model, by applying an approach from a life-cycle perspective when addressing the system cost. From such a point of view, all costs and revenues throughout the lifetime of the system should be considered, that is, initial investment, expected incomes, and costs from electricity sale or purchase, operation, and maintenance costs, component replacement (if required) and component sale at the end of the lifetime [19,33]. Another aspect worth highlighting is the use of real data with an hourly accuracy, allowing the model to compute the hourly discrimination electricity tariffs and market price, as well as the daily and seasonal patterns of involved stochastic RESs, solar irradiation, and wind speed.…”
Section: Introductionmentioning
confidence: 99%